Evaluación de las incertidumbres asociadas con la medición de actividad de radiofármacos (2021)
In nuclear medicine and radiopharmacy, the measurement of radiopharmaceutical radioactivities using dose calibrators (ionization chambers) constitutes a daily practice. These measurements are essential to know the amount of radioactive material applied to radionuclide therapy patients and those having diagnostic support images taken. Using the results of quality controls, we evaluate the performance of a group of dose calibrators that belongs to the Instituto Nacional de Cancerología (INC). We designed and implemented testing protocols to statistically assess the annual performance of dose calibrators, including geometries of clinical interest, the time evolution of daily radioactive measurements during a year, radiophar- maceutical varieties, etc. As additional outcomes, we performed and reported an upgraded energy and efficiency calibration of the Well-Type NaI(Tl) scintillation detector of the INC. We also estimated reference levels of administered activities for diagnostic images in PET (Positron Emission Tomography).